Pemberdayaan Guru Di Sekolah Dasar Negeri 1 PanunggalanKecamatan Pulokulon Kabupaten Grobogan - Iswahyudi, Iswahyudi, Prof..Dr.Ngabdul Ngalim, MM, M.Hum, Dr. Suyatmini, M.Si (2016)
This study aimed to describe the pattern of implementation of the empowerment of teachers in SD Negeri 1 Panunggalan Pulokulon District of Grobogan and describing the results of teacher empowerment in SD Negeri 1 Panunggalan Pulokulon Subdistrict Grobogan. This type of research is qualitative research design using an ethnographic approach. Methods of data collection is done by interviews, observation and documents. The analysis method is interactive analysis. The results of the study patterns of implementation of teacher empowerment in SD Negeri 1 Grobogan Panunggalan, the normal pattern of administrative empowerment of teacher learning collective or group. School principals are familiar approach for the delivery to the teachers of the dialogue or two-way communication. Based on documents study conducted by researchers, the results of teacher empowerment in SD Negeri 1 Panunggalan District of Pulokulon Grobogan include documents fixtures administration learning tools developed by teachers at the beginning of the school year include: syllabus, semester program, mapping standards of competence and basic competence, a minimum completeness criteria and plan the implementation of learning. Using the findings of empowering teachers to improve teacher performance can be seen from the attendance of teachers in schools or in the classroom that is always monitored by the principal.